Aplicativos computacionais para geografia: classificacao multivariada por agrupamento - Gerardi, L. H O; Teixeira, A. L A (My University, 1988)
This paper presents a method for multidimensional classification (Cluster Analysis), as well as a 8 bits microcomputer program in BASIC that automates the process. A practical application of the model is also presented. -English summary
Application programs for geography: cluster analysis
Keywords: cluster analysis; multivariate classification